Indomethacin-Induced Gastric Ulcer in Rats: Gastroprotectivity of Muscari neglectum in Water - Menekse Soydan; Gulnur Arabaci; Necati Utlu; Mesut Bünyami Halici; Esra Aktas Senocak; Metin Kiliçlioglu (Pharmaceuticals)
Background and Objectives: The plant Muscari Mill. is employed in both raw and cooked forms for the treatment of gastric diseases, as an expectorant, and for the treatment of warts and the enhancement of urine. A review of the scientific literature revealed no studies investigating the effect of Muscari neglectum (MN) water extract on gastric diseases. The objective of this study was to determine the effect of a water extract of the MN plant on indomethacin-induced gastric ulcer in rats, using a series of biochemical (SOD, CAT, GSH and MDA levels) and histopathological parameters. Methods: 60 male Sprague Dawley rats were utilized for the purposes of evaluating the acute toxicity and gastric ulcer models, with a total of 36 rats employed for these experiments (n = 6). The rats were divided into six groups: intact; indomethacin; famotidine; indomethacin and MN (100, 200, 400 mg/kg). Results: The Gastric tissue examinations at biochemical, macroscopic and pathological levels showed that MN extracts effectively prevented indo-methacin-induced gastric mucosal damage. The 400 mg/kg dose exhibited the most effective antiulcer effect, with a 69% protective efficacy. This dose caused an increase in the SOD, CAT and GSH levels and a decrease in the MDA levels compared to the IND group. Furthermore, an LC-MS/MS analysis was conducted on the water extract of MN, resulting in the identification of 14 phenolic compounds. Conclusions: Biochemical analyses and histopathological examinations demonstrated that the water extract of MN exhibited a beneficial protective effect against gastric ulceration due to its high antioxidant content.